2005
DOI: 10.1016/j.geoderma.2004.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Time effect on the fractionation of heavy metals in soils

Abstract: Time effect on the fractionation of Cu, Zn, Pb, and Cd in three typical Chinese soils was investigated. A total of 500 mg kg À1 of Cu, Zn, Pb and 2.5 mg kg À1 of Cd were added to soils as nitrates. Metals in the incubated soils were fractionated termly from 3 h to 8 weeks by the sequential extraction procedure, in which the metal fractions were experimentally defined as exchangeable, carbonate-, Fe-Mn oxide-, organic matter-bound and residual fractions. Results showed that the changes of Cu, Pb and Zn in fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
104
5
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(136 citation statements)
references
References 23 publications
24
104
5
3
Order By: Relevance
“…The differences between sorbed Pb and sorbed Cd for a given soil were significant ( p < 0.01; except for those in the Ultisol of Treatments 1 and 2, and those in the Mollisol of Treatment 2). These differences in soil affinity for Pb and Cd have been observed by others for tropical soils and/or pure oxidic mineral systems (Kinneburgh et al, 1976;Puls et al, 1991) as well as for soils low in Fe/Al oxides (Lu et al, 2005;Pardo, 2000). This is usually attributed to differ ences in metal characteristics and resultant affinity for sorption sites McBride, 1994).…”
Section: Pb and CD Affinity For Soil Surfacesmentioning
confidence: 58%
See 1 more Smart Citation
“…The differences between sorbed Pb and sorbed Cd for a given soil were significant ( p < 0.01; except for those in the Ultisol of Treatments 1 and 2, and those in the Mollisol of Treatment 2). These differences in soil affinity for Pb and Cd have been observed by others for tropical soils and/or pure oxidic mineral systems (Kinneburgh et al, 1976;Puls et al, 1991) as well as for soils low in Fe/Al oxides (Lu et al, 2005;Pardo, 2000). This is usually attributed to differ ences in metal characteristics and resultant affinity for sorption sites McBride, 1994).…”
Section: Pb and CD Affinity For Soil Surfacesmentioning
confidence: 58%
“…In several studies, more Cd was found in the exchangeable fraction compared to Pb for soils where heavy metals were added directly (Kaasalainen and Yli-Halla, 2003;Lu et al, 2005), or applied via fly ash (Lim et al, 1997) or biosolids amendments (Sloan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The trend is LF (60 min) <GSF (720 min)≤JB (720 min)<MA (1440 min). Since the rate of metal sorption in soils may be related to its bioavailability (Lu et al 2005), it means that these metals will be more available in the MA soil. It was also observed that the sorption trend for the metals were the same in all soils: Pb(II)>Cu(II)> Cd(II).…”
Section: Cation Sorption Studymentioning
confidence: 99%
“…As for the two soils, the desorption amount of metals from Jiangxi soil decreased less than that from Heilongjiang soil (Table 4). Recently, Lu et al (2004) studied the residence time effect (3 h to 8 weeks) on fractionation and transformation of heavy metals in soils. Metals in soils were fractionated into water soluble, carbonate, Fe-Mn oxide, organic matter and sulfide bound fractions by a sequential extraction method (Tessier et al, 1979).…”
Section: Effect Of Residence Time On Extractability Of Cu CD and Pbmentioning
confidence: 99%